REMOTE SENSING MONITORING OF CHANGES IN SOIL POLLUTION A CASE STUDY IN A REGION IN BAGHDAD, IRAQ - Zaeen, Ahmed; Hadi, Gheidaa (Iraqi Journal of Science, 2024)
One of the main environmental problems which affect extensively the areas in theworld is soil salinity. Traditional data collection methods are neither enough forconsidering this important environmental problem nor accurate for soil studies.Remote sensing data could overcome most of these problems. Although satelliteimages are commonly used for these studies, however there are still needs to find thebest calibration between the data and real situations in each specified area. Landsatsatellite (TM & ETM+) images have been analyzed to study soil pollution(Exacerbation of salinity in the soil without the use of abandoned agricultural for along time) at west of Baghdad city of Iraqi country for the years 1990, 2001 & 2007.All of the three scenes consist six bands (without the thermal band), changes aredetermined by applying supervised classification (Maximum Likelihood) technique.Then using Raster to Vector (R to V) Transform technique. ArcGIS 9.1 program isused to apply the supervised classification and the R to V transforms techniques inorder to determine the results.